The picture of abjection : film, fetish, and the nature of difference - Chanter, Tina, 1960- (Indiana University Press, 2008)
Tina Chanter resolves a fundamental problem in film theory by negotiating a middle path between "gaze theory" approaches to film and spectator studies or cultural theory approaches that emphasize the position of the viewer and thereby take account of race, class, gender, and sexuality. Chanter argues that abjection is the unthought ground of fetishistic theories. If the feminine has been the privileged excluded other of psychoanalytic theory, fueled by the myth of castration and the logic of disavowal, when fetishism is taken up by race theory, or cultural theory, the multiple and fluid registers of abjection are obscured. By mobilizing a theory of abjection, the book shows how the appeal to phallic, fetishistic theories continues to reify the hegemonic categories of race, class, sexuality, and gender, as if they stood as self-evident categories